Epstein-Barr virus lytic replication and cancer - Li, Hao; Lee, Chih-Ying; Delecluse, Henri-Jacques (Current opinion in virology, 2025)
Epidemiological studies have provided strong evidence that Epstein-Barr virus (EBV) lytic replication is linked to cancer development. Evidence of abortive lytic replication in some tumors and infections with recombinant viruses incapable of lytic replication in animal models have reinforced this view. Furthermore, multiple lytic proteins have been shown to induce genetic instability, a well-characterized precancerous state. In particular, lytic proteins dysregulated the DNA damage response, interfered with cell cycle progression, and induced the development of structural genetic abnormalities. However, there is so far no direct evidence from in vivo or in vitro studies that lytic replication alone can induce cancer. Here, we critically review the currently available evidence that EBV lytic replication contributes to cancer development and suggest future research directions.